1993
DOI: 10.1002/cne.903340307
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that cholinergic axons from the parabrachial region of the brainstem are the exclusive source of nitric oxide in the lateral geniculate nucleus of the cat

Abstract: We investigated the source of axons and terminals in the cat's lateral geniculate nucleus that stain positively for NADPH-diaphorase. The functional significance of such staining is that NADPH-diaphorase is identical to the enzyme nitric oxide synthetase, and thus it is thought to reveal cells and axons that use nitric oxide as a neuromodulator. Within the lateral geniculate and adjacent perigeniculate nuclei, a dense network of axons and terminals is labeled for NADPH-diaphorase. The pattern of NADPH-diaphora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
3

Year Published

1995
1995
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 61 publications
6
94
3
Order By: Relevance
“…The aforementioned data suggest that the n.Pvt constitutes one of the principal targets in the midline-intralaminar complex of afferents presumed to generate NO. NO in the lateral geniculate body derives exclusively from neurons that cosynthesize ACh (Bickford et al, 1993). The following observations, however, indicate that the principal source of mesopontine afferent projection to the n.Pvt is noncholinergic.…”
Section: Nadphdmentioning
confidence: 67%
See 2 more Smart Citations
“…The aforementioned data suggest that the n.Pvt constitutes one of the principal targets in the midline-intralaminar complex of afferents presumed to generate NO. NO in the lateral geniculate body derives exclusively from neurons that cosynthesize ACh (Bickford et al, 1993). The following observations, however, indicate that the principal source of mesopontine afferent projection to the n.Pvt is noncholinergic.…”
Section: Nadphdmentioning
confidence: 67%
“…The functional significance of the dense monoaminergic and NADPH-d positive plexi in the n.Pvt and striking spatial overlap with cholinergic processes in the central media1 intralaminar nucleus is unknown. We can predict, based on our structural data, that interactions attributed to the mesopontine source of NO in the LGN (P-ape and Mager, 1992;Bickford et al, 1993) may also apply to actions on nonspecific thalamosensory neurons in the midline-intralaminar complex.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although NADPH-diaphorase staining is developmentally regulated in LGN cells, staining is present in the neuropil in the LGN at all ages . Neuropil staining arises from cholinergic brainstem projections (Bickford et al, 1993). Because blockade of NOS at early ages does not interfere with the formation of eye-specific layers, it is unlikely that NO produced in the neuropil is involved in early retinogeniculate pattern formation.…”
Section: Discussionmentioning
confidence: 99%
“…Within the ventrolateral geniculate nucleus, a dense network of axons and terminals was revealed by staining for NADPH-d in this study. Bickford et al [2] found that parabrachial cells were co-localizd with NADPH-d and ChAT, and the cholinergic cells of the parabrachial region are essentially the sole source of NADPH-d in the lateral geniculate nucleus. They also reported that NADPH-d-positive cells in the parabrachial region were not labeled for 5-HT.…”
Section: Considerable Relationship Between Nadph-d-positive Neurons Amentioning
confidence: 99%